Kajian Aksiologi tentang Kontribusi dan Kontroversi Pemanfaatan Amonia dari Proses Haber-Bosch - Abdul Latip (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
The purpose of this article is to conduct an axiological study of the Haber-Bosch process. The Haber-Bosch process had both contributions and controversies early on in its discovery. The study in writing this article uses a literature review which consists of selecting the topic to be reviewed, searching and selecting articles related to the topic, analyzing and synthesizing the literature, and organizing the writing. The literature reviewed relates to the main themes, namely the Haber-Bosch process, the use of Haber-Bosch products, and axiological studies on Haber-Bosch products. The results of the axiological study show that: 1) The breakthrough from Haber-Bosch related to ammonia production provides benefits for the sustainability of the agricultural sector and the survival of European society. In the current context, the Haber-Bosch process has both theoretical and practical uses. 2) On the other hand, the Haber-Bosch process is used by Haber to maintain the supply of gunpowder and manufacture toxic gases used as chemical weapons that killed hundreds of thousands of people. This certainly shows something unethical and shows a scientific paradoxaxiology; Haber; Bosch; Ammonia